Feed consumption and weight gaining behavior of zucker fatty (fa/fa) rats with single and in combination treatment of clonidine and metformin - Rajput, Ranjitsinh M. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diabetes is metabolic disorder with high blood glucose level. Type-2 diabetes is associated with obesity, insulin resistance, and chronic hyperglycemia. So agents that are efficiently reduces weight gain along with diabetic control may play beneficial role in obese diabetic subjects. Methods: Zucker Fatty Rats were used for the study. Animals were divided in four groups, (control group, Clonidine group, metformin group and combination group). Normal weight gain and feed consumption data were obtained up to 9 weeks of age there after animals were started treatment according to above mentioned groups. During treatment again feed consumption and weight gain data were generated. The experimental results are expressed as the Mean ± SEM in each group. Statistical analysis has been performed by one way analysis of variance (ANOVA). Results: The data suggest that there is decrease in body weight gain during the treatment with clonidine and in combination of clonidine and metformin. If we consider weight gain of control as 100 % weekly than clonidine group shows 10.45 % weight gain while metformin shows 96.5 % weight gain and in combination group it shows 33.63 % weight gain. So, there is significant reduction in weight gain of the group treated with clonidine and combination of clonidine and metformin. Same time there is reduction in feed consumption of animals. Conclusions: The centrally acting drug Clonidine affects the feed consuming behavior and weight gain of animals. It shows hypophagic effect and reduces weight gain in single as well as in combination with metformin.